2020
DOI: 10.1108/srj-10-2019-0336
|View full text |Cite
|
Sign up to set email alerts
|

CSR in developing countries – the importance of good governance and economic growth: evidence from Africa

Abstract: Purpose The purpose of this study is to examine the effect of public governance and economic growth on corporate social responsibility (CSR) performance in Egypt, Morocco, Mauritius, Nigeria and South Africa. It also assesses the trend of CSR performance in these countries over time. Design/methodology/approach The study is based on a sample of five countries in Africa for the period 2012-2017. The multivariate regression model was used in testing the research questions/hypotheses. Robustness tests were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 54 publications
(71 reference statements)
0
19
0
Order By: Relevance
“…This finding is rather disappointing, keeping in view the poor climatic conditions of Pakistan, because small-sized enterprises in Pakistan exist in large numbers, and if such a large number are neglecting the environment, then it will be very difficult for the country to hope for a better and sustainable future. There are studies in the extant literature that also confirmed that environmental improvement through CSR is something that is not the priority of most developing countries in the world [73,74]. These results are dissimilar with the studies in developed countries, where many of steps have been taken to improve the environmental footprint of the enterprises through CSR [75,76].…”
Section: Discussionmentioning
confidence: 88%
“…This finding is rather disappointing, keeping in view the poor climatic conditions of Pakistan, because small-sized enterprises in Pakistan exist in large numbers, and if such a large number are neglecting the environment, then it will be very difficult for the country to hope for a better and sustainable future. There are studies in the extant literature that also confirmed that environmental improvement through CSR is something that is not the priority of most developing countries in the world [73,74]. These results are dissimilar with the studies in developed countries, where many of steps have been taken to improve the environmental footprint of the enterprises through CSR [75,76].…”
Section: Discussionmentioning
confidence: 88%
“…The state of CSR affairs is very poor in most developing countries, and a lot of inconsistencies in this connection have been reported by contemporary CSR researchers [ 9 , 10 ]. Further, most of the previous studies in the domain of CSR in developing countries context have largely addressed the relationship of CSR with a philanthropic mindset [ 11 , 12 , 13 ] but its important relationship to improve the natural environment is still under-explored. Likewise, the prior studies investigated the phenomenon of CSR at a macro or organizational level but its contribution at the individual (employee) or micro-level is something that has not received the due attention of modern researchers.…”
Section: Introductionmentioning
confidence: 99%
“…The contributions of the present study to the recent literature are many, for example, the present study enriches the existing CSR literature from the perspective of MCSR, whereas the majority of previous studies have considered this under the domain of macro or institutional level [ 11 , 12 , 13 ]. In the same vein, the present study adds significantly to existing CSR literature by proposing the relationship of MCSR to shape the pro-environmental behavior of employees at the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…", as well as the procedures for making decisions in the company's affairs, setting the regulations, creating the objectives, strategies needed to achieve them, and the foundation for performance evaluation." [17,18,19].…”
Section: Background Theoreticalmentioning
confidence: 99%